Breast conservation therapy after neoadjuvant chemotherapy: Optimization of a multimodality approach. Issue 1 (13th March 2014) - Caudle, Abigail S.; Kuerer, Henry M.; Rubio, Isabel T.; Dixon, J. Michael
Abstract Neoadjuvant chemotherapy (NAC) is routinely used in locally advanced breast cancer, but is increasingly used in early stage patients. Even patients with advanced disease can achieve excellent outcomes with breast conservation therapy (BCT) after NAC. The use of NAC followed by BCT is an example of how multimodality therapy can optimize outcomes while limiting morbidity and preserving cosmetic outcomes. Open communication between the multidisciplinary team is crucial to selecting appropriate candidates for this approach. J. Surg. Oncol. 2014 110:32–36. © 2014 Wiley Periodicals, Inc.